The Influence of Gotong Royong Culture on the Use of Accounting Information Systems Mediated by Perception of Usefulness and Perception of Ease of Use - Nikmatuniayah; Marliyati; Handayani, Jati; Anugrahwati, Lilis Mardiana; Titanya, Dara Avril (Yayasan Ilomata, 2025)
Siskeudes, which is a village financial system implemented by the local government to record and report transactions for accountability of the use of village funds, is important for village officials to be accountable for its implementation. This system is expected to provide effective information to villagers. This study aims to test and analyze the influence of cooperation culture, perception of usefulness, and perception of ease of use on the use of Accounting Information Systems (AIS); as well as the indirect influence of cooperation culture on the use of AIS mediated by perception of usefulness and perception of ease of use. This study investigated 10 villages sampled from the Ungaran Timur District, Semarang Regency. Ungaran Timur District was selected because the characteristics of the village are still closely related to the culture of cooperation. The required data were collected by a survey using a questionnaire. The collected data were analyzed using the partial least squares (PLS) Smart 2.0 M3 analysis tool. The results of the study demonstrate that the culture of cooperation influences the perception of usefulness, ease of use, and the use of AIS. Likewise, the perception of the usefulness of AIS affects the use of AIS, except for the ease of use factor.